RELEVANCE OF PANCASILA JUSTICE VALUE IN THE IMPLEMENTATION OF CHEMICAL CRIMINAL SANCTIONS ON SEXUAL CRIMINAL - Aji Sudarmaji (UNISSULA, 2019)
In its development every person in the country of Indonesia has the right to live free from torture and sexual crimes, therefore sexual crimes are damned and heinous acts which must be resisted. All this time, resistance to sexual violence has been carried out by all parties under the existing legal umbrella, including Perpu No. 1 of 2016, namely through the implementation of chemical castration sanctions, but in reality, it has not been effective in eradicating sexual crimes. In addition, the existing castration chemical sanctions are also felt to have violated the human rights of perpetrators of sexual crimes, whereas the actual law only restores the social system of existing crimes by not violating the human rights of all parties, both victims and perpetrators. The purpose of the research in this article is to analyze the formulation of castration sanctions policy policies on the perpetrators of the crime of child sexual violence in Indonesia at this time. To analyze castration criminal sanctions against child sexual violence offenders in Indonesia who have not met Pancasila values. To find the right formula for reconstructing criminal sanctions on perpetrators of child sexual violence in Indonesia based on Pancasila values. The method used in this article is sociological juridical. From the results of the research carried out it can be concluded that the implementation of Article 81 PERPU Number 1 the Year 2016 has not effectively protected and been able to recover victims of sexual violence. Then the factors that influence this are legal regulations that are still contrary to human rights respect as stipulated in the Pancasila and the 1945 Constitution of the Republic of Indonesia, then law enforcement factors that still do not pay attention to the recovery of children who are victims of sexual violence, and factors community culture that is still unable to effectively combat sexual violence against children due to a culture that considers sexual violence against children a family disgrace that no one should know.